Invigoration Treatment of White Jabon (Neolamarckia cadamba (Roxb.) Bosser) Seeds Using Polyethylene Glycol and Ultrafine Bubbles - Nura Aulia Nurul Fata; NFN Supriyanto; Evayusvita Rustam; Dede J. Sudrajat (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
Polyethylene glycol (PEG) and ultrafine bubbles (UFB) can be used to increase seed germination and its vigor. The purpose of this study was to examine the effect of PEG-6000 and UFB on the seed germination and vigor of white jabon after 7 years of storage. This study used a completely randomized design with factorial pattern using two factors, i.e. provenances (Alas Purwo, Kapuas, Kampar, Pomalaa) and invigoration treatments (seed without treatment, PEG -0.8 MPa for 24 h, PEG -1.2 MPa for 24 h, UFB (operating 30 min) for 24 h, UFB (operating 30 min) for 48 h, UFB (operating 55 min) for 24 h, UFB (operating 55 min) for 48 h). UFB treatments had a better effect on white jabon seeds germination compared to PEG. Interaction of Pomalaa provenance seed with soaking in UFB (operating 55 min) for 24 h gave the best germination capacity (87%), germination value (7.35), and seed germination speed (7.39% day-1). While for the very low seed vigor (seed from Alas Purwo, Kampar and Kapuas), the treatment of soaking in UFB water (operating 30 min) for 48 h improved the germination capacity of seed from Alas Purwo (35.50%), Kapuas (35.25%), and Kampar (14.75%).